An Exploratory Study on Retaining Talents in Malaysia : A Case Study of Selected Malaysian Talents - Kok, Phui Fun (2011)
This research is intended as an exploratory case study to convey a qualitative feel on the issue of retention of Malaysian talents still in Malaysia. It fills a gap not covered by the World Bank’s “Malaysia Economic Monitor: Brain Drain” report, in order to give some insights to individual companies in Malaysia concerning the retention of their existing talents, provide some food for thought for other stakeholders, and spur ideas for more in-depth study in the future.It examines how salary and benefits, career prospects and opportunities, and quality of life (factoring in working experience abroad) impact upon the retention of Malaysian talents, specifically on their decision to stay and work in their organisations in Malaysia now and intention to leave their organisations and Malaysia in the foreseeable future and why. Findings are that respondents were generally satisfied with the three reasons or factors of salary and benefits, career prospects and opportunities, and quality of life, and that working experience abroad appeared to increase satisfaction with some dimensions within the three factors but also increase willingness to consider migration in future. The snapshots which emerged show that satisfaction translates into commitment and leads to retention: satisfaction with salary and benefits (to a lesser extent), and career prospects and opportunities and quality of life (to a greater extent) has led to the respondents’ decision to stay and work for their rganisations in Malaysia now (reinforced by working experience abroad), and their intention to continue staying in the foreseeable future (though somewhat mitigated by working experience abroad).